Implementation of the Policy for Strengthening Teacher Competence through Continuous Competence Development (PKB) Based on East Java Governor Regulation No. 38/2024 in Surabaya: Implementasi Kebijakan Penguatan Kompetensi Guru melalui Pengembangan Kompetensi Berkelanjutan (PKB) Berdasarkan Pergub Jatim No. 38/2024 di Surabaya - Nihe, Andini Sukmawati; Purwoko, Budi; Hazin , Mufarrihul (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
This study aims to analyze the implementation of East Java Governor Regulation Number 38 of 2024 concerning Strategic Planning for Vocational Education and Vocational Training, specifically in strengthening teacher competency through the Continuous Professional Development Program (PKB) in Surabaya. The urgency of this study arises from the lack of empirical studies analyzing this latest regional regulation, even though this policy is crucial for ensuring teachers are adaptive to global industry needs. The method used is a qualitative study with a systematic literature review approach, using the Mazmanian & Sabatier implementation theory framework to evaluate policy documents, program reports, and related research. The main findings indicate that the policy implementation has been very effective and directed, driven by three key factors: a strong regulatory structure, active synergy between the Education Office and the industrial world (including PT PAL and PT INKA), and a high commitment from implementers. This effectiveness is measured by the PKB achievements, such as more than 500 vocational high school teachers participating in digital literacy training and the production of more than 250 scientific publications for teachers. A significant contribution of this study is the affirmation of a model for teacher competency development that is integrated between schools and industry demands. The implications require increased budgets to expand access to quality training and strengthen technological infrastructure to ensure the sustainability of PKB in the future.